(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Anesthetic management of patients with dilated cardiomyopathy (DCM) is a challenge to theanesthesiologist, due to poor left systolic function, ventricular enlargement, risk of malignant arrhythmiasand sudden cardiac death. Therefore, preoperative assessment and appropriate anesthetic managementare important in patients with DCM. Five to eight people per 100,000 develop this disorder each year.Malignant arrhythmias are the most common cause of death in DCM.1 Around 50% of cases ofnonischaemic dilated cardiomyopathy is idiopathic. Other causes are familial, infectious, infiltrativeand connective tissue diseases. This is a report of successful anesthetic management of a patient withsevere DCM undergoing laparoscopic cholecystectomy using general anesthesia (GA). JBSA 2018; 31(2): 95-98